Կուսակցությունների տիպավորման գաղափարաքաղաքական սկզբունքի կիրառման հարցի շուրջ | - Քեռյան, Գարիկ (YSU Journal of International Affairs, 2014)
Political and ideological principles are one of the main criteria for the typology of political parties. According to the classification by political and ideological principles, the first group consists of doctrinal parties with certain and officially proclaimed ideology. The second group includes parties with uncertain ideology, which we prefer to regard as pragmatic ones. Classification of political parties can be based either on the ideological specifics of political parties, or on the essence of developed policies /liberal, socialist, conservative, religious, nationalist, etc./.
Keywords: political parties, typology, ideology of political parties, doctrinal and pragmatic parties, policy, principles of functioning